John Locke’s Paraphrase and Notes on the Epistles of St. Paul in the Intellectual Culture of the Eighteenth-Century Church of England, 1707–1800 - Chatterjee, Jacob Donald (Locke Studies, 2024)
This article presents a new account of the reception of John Locke’s Paraphrase and Notes on the Epistles of St. Paul (1705–7) in the eighteenth-century Church of England. Although the Paraphrase is rarely discussed in studies of the influence of Locke’s writings, this work was widely used by later scholars and clergymen. The fierce early response to the Paraphrase’s apparently heterodox interpretations of St. Paul’s accounts of the Resurrection and the Trinity soon gave way to a more positive appreciation of the work’s merits. Even in these early years, some putatively orthodox divines had found much that was useful in the Paraphrase. After 1730, such positive readings of the Paraphrase became more prevalent. The growing status of Locke’s philosophy facilitated a re-reading of his religious writings. The Paraphrase was lauded in Biblical commentaries, educational writings, sermons, and systematic treatises. Scholars and clergymen frequently imbibed Locke’s hermeneutic principles; his judicious comments on St. Paul’s style and argumentative strategy; his anti-Calvinist exegesis; and, the contextual knowledge he provided for understanding the epistles. The enduring influence of the Paraphrase also ensured that it was deployed in several significant theological debates around Deism and obligatory subscription to articles of faith.